Eye Size Affects Cuteness in Different Facial Expressions and Ages - Yao, Lichang; Dai, Qi; Wu, Qiong; Liu, Yang; Yu, Yiyang; Guo, Ting; Zhou, Mengni; Yang, Jiajia; Takahashi, Satoshi; Ejima, Yoshimichi; Wu, Jinglong (Frontiers in Psychology, 2022)
Researchers have suggested that infants exhibiting baby schema are considered cute. These similar studies have mainly focused on changes in overall baby schema facial features. However, whether a change in only eye size affects the perception of cuteness across different facial expressions and ages has not been explicitly evaluated until now. In the present study, a paired comparison method and 7-point scale were used to investigate the effects of eye size on perceived cuteness across facial expressions (positive, neutral, and negative) and ages (adults and infants). The results show that stimuli with large eyes were perceived to be cuter than both unmanipulated eyes and small eyes across all facial expressions and age groups. This suggests not only that the effect of baby schema on cuteness is based on changes in a set of features but also that eye size as an individual feature can affect the perception of cuteness.